Assessment of chemically characterised Abelmoschus moschatus Medik. seed essential oil as shelf life enhancer of herbal raw materials based on antifungal, antiaflatoxigenic and antioxidant efficacy. (2nd January 2017) - Dwivedy, A. K.; Kumar, M.; Kedia, A.; Mishra, P. K.; Chanotiya, C. S.; Dubey, N. K.
Abstract: The study reports fungal biodeterioration of herbal raw materials of Adhatoda vasica Nees and Withania somnifera Dunal and assessment of Abelmoschus moschatus Medik seed essential oil (AMEO) as antifungal, antiaflatoxigenic, and antioxidant. Seven fungal species belonging to three genera were isolated from Adhatoda vasica leaves and Withania somnifera roots. The minimum inhibitory, fungicidal, and aflatoxin inhibitory concentrations of AMEO were found to be 1750, 5000, and 1250 ppm, respectively, against A. flavus LHP-WS-1, isolated from W. somnifera . The effect of AMEO over ergosterol content in the plasma membrane was assessed to test the mode of action on A. flavus . AMEO also exhibited broad fungitoxicity at its minimum inhibitory concentration (MIC) and strong antioxidant property through 2, 2-diphenyl-1-picrylhydrazyl (DPPH) analysis having IC50 value equal to 0.325 μL/mL. In view of strong antifungal, antiaflatoxigenic, and antioxidant activity, the AMEO may be recommended as botanical preservative for herbal raw materials in order to enhance their shelf life and to maintain their quality.